2020
DOI: 10.1111/ppa.13290
|View full text |Cite
|
Sign up to set email alerts
|

Argentinian potato leafroll virus P0 protein: Novel activities for a previously known suppressor

Abstract: The potato leafroll virus (PLRV) P0 protein (P0PL) is a suppressor of RNA silencing. In this study, we showed that P0 protein from an Argentinian isolate of PLRV (P0PL‐Ar) has an additional activity not described for other PLRV or P0 proteins from poleroviruses. Besides reporting that P0PL‐Ar displays both local and systemic silencing suppressor activity, we demonstrated, for the first time, that P0PL‐Ar impedes accumulation of dsRNA‐derived siRNAs. We also showed that P0PL‐Ar interacts with Solanum tuberosum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The Argentinian PLRV isolate P0 protein (P0 PL‐Ar ), which has F‐box and WG domains, displays intermediate silencing suppressor activity both locally and systemically and, according to an inverted repeat assay, inhibits the production of siRNAs from dsRNA. These results indicate that, unlike other P0 proteins of previously characterized poleroviruses, P0 PL‐Ar would act at more than one step of the silencing path, upstream of dicer‐like protein (DCL)‐mediated primary siRNA production and at the RISC complex level, by decreasing AGO1 accumulation (Barrios Barón et al, 2021).…”
Section: Characteristics Of Proteins Encoded By Polerovirusesmentioning
confidence: 86%
See 3 more Smart Citations
“…The Argentinian PLRV isolate P0 protein (P0 PL‐Ar ), which has F‐box and WG domains, displays intermediate silencing suppressor activity both locally and systemically and, according to an inverted repeat assay, inhibits the production of siRNAs from dsRNA. These results indicate that, unlike other P0 proteins of previously characterized poleroviruses, P0 PL‐Ar would act at more than one step of the silencing path, upstream of dicer‐like protein (DCL)‐mediated primary siRNA production and at the RISC complex level, by decreasing AGO1 accumulation (Barrios Barón et al, 2021).…”
Section: Characteristics Of Proteins Encoded By Polerovirusesmentioning
confidence: 86%
“…This was evidenced by western blot analyses in which the studied P0 mutants unable to interact with SKP exhibited reduced or no accumulation in N. benthamiana leaves; similar results were obtained for P0 CLRDV F-box mutants (authors' unpublished data) in contrast to some F-box mutants of the Argentinian isolates of PLRV (P0 PL-Ar ). In the case of P0 PL-Ar , studies showed that not only residues L76P77, but also the GW/WG motif, both within the F-box domain, may be involved in this difference (Barrios Barón et al, 2021).…”
Section: Er-associated Bodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some viruses have evolved to exploit these host mechanisms to degrade proteins involved in the RNA silencing pathway. For example, P0 proteins of viruses in the genera Polerovirus and Enamovirus may target and degrade AGO1 through the autophagy pathway ( Derrien et al., 2012 ; Fusaro et al., 2012 ; Michaeli et al., 2019 ; Barrios Barón et al., 2021 ), while PVX P25 destabilizes AGO1 via the 26S proteasome pathway ( Chiu et al., 2010 ). TuMV P1/HC-Pro degrades AGO1 through autophagy ( Hu et al., 2020 ; Hong et al., 2023 ), and TuMV VPg interacts with, and induces the degradation of SGS3 through both proteasome and autophagy pathways ( Cheng and Wang, 2017 ).…”
Section: Discussionmentioning
confidence: 99%